Analisis Faktor yang Mempengaruhi Kualitas Hidup Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa - Yunita, Yunita; Najihah, Najihah; Wijayanti, Dewi; Lesmana, Hendy (Universitas Malahayati, 2024)
ABSTRACT Chronic Kidney Failure occurs due to irreversible deterioration in kidney function that occurs over several months or years. This situation results in an inability to maintain the balance of body substances or an accumulation of fluid and waste products which requires kidney replacement or dialysis therapy. Hemodialysis therapy is a replacement therapy to remove metabolic waste from the human blood circulation which will affect the quality of life. The aim of this study was to identify factors associated with quality of life in chronic kidney failure patients undergoing hemodialysis at RSUD dr. H. Jusuf SK North Kalimantan. This research is a descriptive study with a cross sectional study design. Sampling used purposive sampling. The samples in this study were patients undergoing hemodialysis therapy at RSUD dr. H. JUSUF SK North Kalimantan, totaling 100 respondents. Data were collected using a questionnaire from WHOQoL. The results of the study showed that there was no relationship between age and employment with a p value of 0.369 and 0.398, whereas gender, education, duration of HD, frequency of HD were found to have a relationship with each p value of 0.036; 0.011; 0.034 and 0.008. It can be concluded that there is a significant relationship between gender, education, duration of hemodialysis and frequency of hemodialysis and the quality of life of patients undergoing hemodialysis at RSUD dr. H. Jusuf SK. Therefore, it is hoped that nurses and other health workers will provide education regarding the importance of HD and increase family participation as a support system to improve the patient's quality of life. Keywords: Quality of Life, Chronic Renal Failure, Hemodialysis ABSTRAK Gagal Ginjal Kronik terjadi karena kemunduran fungsi dari ginjal ireversibel yang terjadi beberapa bulan atau tahun. Keadaan ini mengakibatkan ketidakmampuan dalam mempertahankan keseimbangan substansi tubuh atau akumulasi cairan dan produk sisa yang memerlukan penggantian ginjal atau terapi dialysis. Terapi hemodialisis merupakan terapi pengganti untuk mengeluarkan sisa-sisa metabolisme dari peredaran darah manusia yang akan mempengaruhi kualitas hidup. Tujuan penelitian ini untuk mengidentifikasi faktor yang berhubungan dengan kualitas hidup pada pasien gagal ginjal kronik yang menjalani hemodialisa di RSUD dr. H. Jusuf SK Kalimantan Utara. Penelitian ini merupakan penelitian deskritif dengan desain cross sectional study. Pengambilan sampel menggunakan purposive sampling. Sampel dalam penelitian ini adalah pasien yang menjalani terapi hemodialisis di RSUD dr. H. JUSUF SK Kalimantan Utara yang berjumlah 100 responden. Pengambilan data menggunakan kuesioner dari WHOQoL. Hasil penelitian menunjukkan bahwa tidak ada hubungan antara usia dan pekerjaan dengan p value 0,369 dan 0,398 sedangkan dengan jenis kelamin, pendidikan, lama HD, frekuensi HD ditemukan ada hubungan dengan masing-masing p value 0,036 ; 0,011; 0,034 dan 0,008. Dapat disimpulkan ada hubungan yang bermakna antara jenis kelamin, pendidikan, lama hemodialisa dan frekuensi hemodialisa dengan kualitas hidup pasien yang menjalani hemodialisa di RSUD dr. H. Jusuf SK. Oleh karena itu, diharapkan agar perawat dan tenaga kesehatan lainnya memberikan edukasi terkait pentingnya HD serta meningkatkan peran serta keluarga sebagai support sistem untuk meningkatkan kualitas hidup pasien. Kata Kunci: Kualitas Hidup, Gagal Ginjal Kronik, Hemodialisa